2020
DOI: 10.3390/v13010021
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus Structural Protein p17 Inhibits Cell Proliferation through ER Stress—ROS Mediated Cell Cycle Arrest

Abstract: African swine fever virus (ASFV) is a highly pathogenic large DNA virus that causes African swine fever (ASF) in domestic pigs and wild boars. The p17 protein, encoded by the D117L gene, is a major transmembrane protein of the capsid and the inner lipid envelope. The aim of this study was to investigate the effects of p17 on cell proliferation and the underlying mechanisms of action. The effects of p17 on cell proliferation, cell cycle, apoptosis, oxidative stress, and endoplasmic reticulum (ER) stress have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…ASFV p17 protein is encoded by the D117L gene and consists of 117 amino acids. There are three glycosylation sites including N12, N61 and N97, and one transmembrane domain (AAs 39-59) (23). We found that the transmembrane domain of p17 is required for interaction with STING and interference with STING in the recruitment of TBK1 and IKKε while the three glycosylation sites are not important.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…ASFV p17 protein is encoded by the D117L gene and consists of 117 amino acids. There are three glycosylation sites including N12, N61 and N97, and one transmembrane domain (AAs 39-59) (23). We found that the transmembrane domain of p17 is required for interaction with STING and interference with STING in the recruitment of TBK1 and IKKε while the three glycosylation sites are not important.…”
Section: Discussionmentioning
confidence: 87%
“…The copyright holder for this preprint this version posted June 5, 2021. ; https://doi.org/10.1101/2021.06.02.446854 doi: bioRxiv preprint 4 study also indicated that p17 protein could inhibit cell proliferation by inducing cell cycle arrest via ER stress-ROS pathway (23).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…First, it was evidenced by MTT assay that the maximum safety concentration of TTO was 0.063% (wt/wt), and CC50 was 0.32%. As an obligate intracellular pathogen, the proliferation of VSV strictly depends on its internal replication in living cells ( 26 ). Therefore, the level of its replication rate is an intuition index for the study of the antiviral effect of TTO.…”
Section: Discussionmentioning
confidence: 99%
“…This new method first induces a specific double-strand DNA break (DSB) by an RNA-guided nuclease, then enables genome editing by repairing DSB via either error-prone non-homologous end joining (NHEJ) or homology-directed repair (HDR). Several recombinant herpes viruses, including HSV-1, were produced using the CRISPR-Cas9 system and can be used to conduct virus-host interaction studies 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%